Assessment of Bacteria in Panulirus ornatus and Panulirus homarus Lobsters Infected with Milky Disease in Floating Net Cage Culture Media - Nunik Cokrowati; Muhammad Junaidi; Muhammad Marzuki; Muhammad Sumsanto; Aprililianti (Journal of Aquaculture and Fish Health, 2026)
West Nusa Tenggara consists of the islands of Sumbawa and Lombok. It has lobster resources in the waters of both islands. Lobster production in West Nusa Tenggara comes from wild catches and aquaculture. Lobster production in Lombok reaches more than 150 tons per year, including the species Panulirus Homarus and Panulirus ornatus. Lobster aquaculture in Lombok is carried out using a floating net cage system. The challenge in lobster aquaculture is the emergence of milky disease. This disease is caused by Rickettsia-like organisms (RLO) bacteria that attack lobster body tissue, especially in the hemolymph. The impact of milky disease is very significant, especially on lobster aquaculture productivity. The purpose of this study was to analyze the abundance and types of bacteria in Panulirus Homarus and Panulirus ornatus lobsters infected with milky disease and in the seawater used for cultivation. Bacterial assessment of lobsters infected with Milky Disease is necessary to identify the bacteria causing MHD-SL and the prevalence of lobsters infected with MHD-SL. This bacterial assessment was conducted on seawater used for lobster cultivation in lobster net cages and on the meat of lobsters infected with MHD-SL. The results of the assessment can be used to determine preventive measures that can be taken to prevent MHD-SL infection. The advantage of the solution offered in this study is that bacterial assessment is carried out on seawater used for cultivation in floating net cages and bacterial analysis is also carried out on lobsters infected with MHD-SL. This research will be conducted at the floating net cages of PT. Pasopati Indo Kreasi in the waters of Gili Gede Sekotong, the University of Mataram fish health laboratory, and the Lombok Marine Aquaculture Testing Laboratory. The research method used is an experimental method conducted at sea and in the laboratory. The expected research results are the abundance and types of bacteria in lobsters infected with milky disease and in the seawater at the cultivation site.